Kansas Land Prices and Cash Rental Rates - Taylor, Mykel (My University, 2015)
This farm management guide reports Kansas land prices and cash rental rates for 1995-2014. The data is meant to be useful to farm managers.
MF1100_2015_06
Keywords: MF1100; Economics; MF